Soil microbial succession along a chronosequence on a High Arctic glacier foreland, Ny-Ålesund, Svalbard: 10 years’ change - Yoshitake, Shinpei; Uchida, Masaki; Iimura, Yasuo; Ohtsuka, Toshiyuki; Nakatsubo, Takayuki (Polar Science, 2018)
Rapid glacial retreat in the High Arctic causes the expansion of new habitats, but the successional trajectories of soil microbial communities are not fully understood. We examined microbial succession along a chronosequence twice with a 10-year interval in a High Arctic glacier foreland. Soil samples were collected from five study sites with different ages and phospholipid fatty acids analysis was conducted to investigate the microbial biomass and community structure. Microbial biomass did not differ significantly between the two sampling times but tended to increase with the chronosequence and showed a significant correlation with soil carbon (C) and nitrogen (N) content. Microbial community structure clearly differed along the chronosequence and was correlated with C and N content. The largest shift in community structure over 10 years was observed in the newly exposed sites after deglaciation. The accumulation of soil organic matter was regarded as an important determinant both of microbial biomass and community structure over the successional period. In contrast, the initial microbial community on the newly exposed soil changed rapidly even in the High Arctic, suggesting that some key soil processes such as C and N cycling can also shift within the relatively short period after rapid glacial retreat. journal article